2013
DOI: 10.1002/aenm.201300449
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Nanostructure and Recombination Dynamics in a Low‐Temperature Solution‐Processed CuInS2 Nanocrystalline Solar Cell

Abstract: The understanding and control of nanostructures with regard to transport and recombination mechanisms is of key importance in the optimization of the power conversion efficiency (PCE) of solar cells based on inorganic nanocrystals. Here, the transport properties of solution‐processed solar cells are investigated using photo‐CELIV (photogenerated charge carrier extraction by linearly increasing voltage) and transient photovoltage techniques; the solar cells are prepared by an in‐situ formation of CuInS2 nanocry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 47 publications
7
51
1
Order By: Relevance
“…A suppressed, non-Langevin recombination coefficient (with β < β L ) has been reported in organic photovoltaic blends that exhibit high performance. [6][7][8][9][10] Suppressed recombination is desirable to ensure efficient charge extraction. The reduction factor β/β L is a useful "figure of merit" for screening candidate photovoltaic blends to rapidly identify those which are likely to be highly performing.…”
Section: Introductionmentioning
confidence: 99%
“…A suppressed, non-Langevin recombination coefficient (with β < β L ) has been reported in organic photovoltaic blends that exhibit high performance. [6][7][8][9][10] Suppressed recombination is desirable to ensure efficient charge extraction. The reduction factor β/β L is a useful "figure of merit" for screening candidate photovoltaic blends to rapidly identify those which are likely to be highly performing.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work demonstrated that indiumon-copper-antisites (In Cu ) and copper vacancies (V Cu ) are the dominant donors and acceptor defects, respectively, in ternary chalcopyrite CIS and CISe. [ 16,17 ] Even ordered defect stoichiometries such as CuIn 5 Se 8 or CuIn 5 S 8 may form.…”
mentioning
confidence: 99%
“…Azimi et al suggested that the organic reagents present in the as-prepared film were removed by the second annealing process. 37 A void surface might help form an interpenetrating heterojunction during the CdS buffer-layer deposition to facilitate effective charge separation at the large area junction; however, in view of our cell configuration (Au/CIS/CdS/ZnO NR/ITO), a porous surface might deteriorate the cell performance because gold electrodes that deeply penetrate the voids in a CIS surface can form shunt paths through direct contact with the CdS buffer layer.…”
Section: Resultsmentioning
confidence: 98%